Persistência poliglota em bancos de dados e ferramentas de desenvolvimento de aplicativos - Claro, Carlos Augusto Martins (2017)
With the emergence of new gadgets, numerous platforms, ways to share and display content, companies must be increasingly concerned about being present effectively in all. It is essential to seek speed, performance and usability, maintaining a consolidated basis for consultation and communication with databases. For this we will study the development of applications, with compatibility between gadgets and languages, using a centralized query format, using new technologies, through REST API. To further optimize these deliveries, study, explain how each tool covered works and measure the performance of MySQL and NoSQL databases, suggesting the best tool for each service provided by real estate delivery, through real estate portal research. Exemplifying at the end of the project how we can apply and optimize the real estate query with MongoDB, searching for more accurate suggestions based on related searches in graphos databases Neo4J. And showing how using persistence polyglot we can optimize services and save server resources. Comparing resource application, pre and post polyglot persistence.